Islamic Values-Based Reconstruction of Community Organizations Governnce : The Context of Balancing Freedom of Association and Public Order in Indonesia - Teguh Luhuringbudi; Tri Gunawan; Edi Kurniawan; Nabilah Yusof; Wilnan Fatahillah; Safa Husayn Alrumayh (International Forum of Researchers and Lecturers, 2025)
The rapid changes in Indonesia's socio-political landscape have highlighted the urgency of reconstructing the governance of civil society organizations, especially in balancing the tension between the freedom of association and public order. This tension has emerged as a contemporary trend filled with controversy and civil unrest. This study aims to formulate a model of governance for civil society organizations based on Islamic values, using three theoretical frameworks: Najm al-Din al-Tufi's Maṣlaḥah Theory, Robert Putnam's Civil Society Theory, and Mark Bevir's Good Governance Theory. The methodology used is a qualitative-descriptive approach, which includes data collection through policy documentation, digital media analysis, and in-depth interviews with two key informants from religious-based civil society organizations—Nahdlatul Ulama (NU) and Persatuan Islam (PERSIS). Primary sources include official government documents such as Government Regulation in Lieu of Law (Perpu) No. 2 of 2017 and Minister of Home Affairs Regulation No. 57 of 2017, alongside empirical narratives from community leaders. The research findings suggest that the social legitimacy of civil society organizations is more influenced by the practical application of maqāṣid al-sharī‘ah (obligatory duties) and their ability to address the real needs of society than by mere adherence to administrative regulations. These findings highlight the gap between legality and legitimacy and emphasize that integrating the values of maṣlaḥah (benefit), social capital, and transparency is essential to strengthening civil society in a democratic state. By embedding Islamic values into the governance models, civil society organizations can better serve the community while maintaining democratic principles, creating a more inclusive and beneficial governance framework that aligns with both public needs and Islamic teachings.